Who was the better athlete? Which was the better team? - Mika Hämäläinen (Nakladatelstvi Karolinum, 2022)
Often, there is disagreement about who is the better athlete, or the better team. The aim of this paper is to clarify a recent disagreement between the author (Mika Hämäläinen) and Arvi Pakaslahti about different views of ‘betterness’ in sport competitions. I introduced a ‘three criteria’ model of betterness, which suggested the following three criteria: the official result, the ideally adjudicated result and the display of athletic skills. Pakaslahti criticised my account and introduced his own model, which has two built-in ideals of sport competitions: the Athletic Superiority Ideal and the Just Results Ideal. I argue that when we look behind the terminological differences, there is surprisingly little genuine disagreement between my account and Pakaslahti’s.